SUSTAINABLE PROFESSIONAL DEVELOPMENT FOR AL-QURAN TEACHERS: BRIDGING CULTURAL HERITAGE AND DIGITAL INNOVATION IN ISLAMIC EDUCATION - Izzatul Amalina; Agus Zaenul Fitri; Abad Badruzaman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
The rapid advancement of digital technology has transformed educational practices, including Islamic education, creating new challenges and opportunities for Al-Quran teachers. This study explores a sustainable professional development model that bridges cultural heritage and digital innovation to enhance the quality and adaptability of Al-Quran educators. Using a qualitative literature review approach, the research analyzes scholarly works on teacher professional development, Islamic pedagogy, digital literacy, and cultural-based education. The findings indicate that sustainable professional development should integrate traditional Islamic values, local cultural wisdom, pedagogical competence, and digital technology skills. Such integration enables Al-Quran teachers to preserve the authenticity of Qur’anic learning while responding effectively to contemporary educational demands. Furthermore, collaborative learning communities, continuous training programs, and technology-supported instructional practices are identified as key factors in strengthening teacher professionalism. The study concludes that harmonizing cultural heritage with digital innovation provides a strategic framework for developing competent, adaptive, and future-ready Al-Quran teachers in the era of educational transformation.